Study Results of Research about the Growth Rate of Tree Species in Post-Mining Area - Ingge Dhyan Cakyayanti; Yadi Setiadi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
Mining would give direct negative impact on environmental condition, there are opened soil surface that willincrease surface run-off; change on forest ecosystem and forest ecology stability. Objective on post mining arearehabilitation is to construct post mining area fit in the land purpose. Collection results of researches in growth of manytrees species is important to know the development of technique and detect the success rate with its factors. The objectiveof this research to evaluate result on researches collected.This research was carried out by collect and analyze the resultof growth on many tree species in post mining area on Laboratorium Bioteknologi Hutan dan Lingkungan ; dan PusatPenelitian Sumberdaya Hayati dan Bioteknologi (PPSHB) library, University library and Department ofForestResources ConservationandEcotourism library at Bogor Agricultural University.Many research resulted there wereseveral tree species which used in rehabilitation post mining area were akasia, lamtoro, gamal, sengon, jarak pagar,pulai, gaharu, nyatoh, kapur naga, mindi, melochia, cemara gunung, nyamplung, ubak, rengkat, leban, and waru . Overtailing in post tin mining area akasia, lamtoro, gamal and sengon well grown with Mycofer and compost treatmentbeside that jarak pagar seedlings well grown in mixed ameliorant and anorganic fertilizer tratment. Over batu baratailing, sludge acquition increasing growth of mangium and acacia. Topsoil acquition increasing seedlings growth ofpulai species. FMA inoculation and soil amandement treatments increasing grown of agarwood species. Soilamandement treatment given positive effect on seedlings of nyatoh and kapur naga species. Over post gold mining area,combination of active compost and FMA helped mindi species to grown up. Over post nickel mining area, melochiaspecies well grown in fertilizer treatments, beside that grass controlling system helped cemara gunung grown well. Overpost tin mining area nyamplung, ubak, rengkat, laban and waru grown up with water splash treatment.